Pengaruh Pengetahuan Kewirausahaan dan Karakteristik Wirausaha terhadap Keberhasilan Usaha UMKM di Kecamatan Singaparna - Salsabila Nurbaeti; Rina Madyasari; Alfin Nur Arifah; Yudi Setia Rachmanda (Pusat Riset dan Inovasi Nasional, 2026)
Micro, Small, and Medium Enterprises (MSMEs) make a significant contribution to the Indonesian economy, particularly by increasing Gross Domestic Product (GDP) and creating employment opportunities. The success of MSMEs is influenced by various factors, including entrepreneurial knowledge and entrepreneurs’ characteristics. This study aims to examine the effect of entrepreneurial knowledge and entrepreneurs’ characteristics on the business success of MSMEs in Singaparna District. The study employed a quantitative approach using a causal associative method. The research sample consisted of 97 MSME owners selected through a purposive sampling technique, while the sample size was determined using Cochran’s formula. Data were collected through a questionnaire using a five-point Likert scale and analyzed with SPSS version 25. The findings indicate that entrepreneurial knowledge does not have a significant effect on the business success of MSMEs. In contrast, entrepreneurs’ characteristics have a positive and significant effect on business success and represent a more dominant factor than entrepreneurial knowledge. These findings suggest that the success of MSMEs is more strongly influenced by entrepreneurs’ characteristics, such as attitudes, behavior, and managerial abilities, than by entrepreneurial knowledge alone. Therefore, developing entrepreneurial characteristics should become a priority in efforts to enhance the success and competitiveness of MSMEs.